Design and Construction of Transistor Based Water Level Indicator Tank with Overflow Alarm - Olawale J. OLALUYI; Johnson O. ADEOGO; Aduragbemi F. OJO; Olarewaju T. OGINNI (FUDMA Journal of Engineering and Technology, 2025)
The use of a sensor controlling water overflow in a tank offers several significant benefits, primarily focusing on water conservation, cost savings, convenience, and safety. This paper discusses the design and implementation of a low-cost, transistor-based water tank overflow alarm (TBWTOA) and a multi-level indicator system (MLIS) that prevent losses by providing real-time monitoring and timely alerts. The system provides a reliable, automated solution to problems associated with manually monitoring water levels. The system employs four conductive probes positioned at low, medium, full, and overflow levels inside the tank. Probes were connected to the base of a BC547 NPN transistor through current-limiting resistors. When water bridges a probe to the common supply, it delivers sufficient base current to saturate the transistor, allowing collector current to flow and illuminate corresponding LEDs: red for low, yellow for medium, blue for full, and green for overflow. At the overflow threshold, the same circuit simultaneously activates a 5V buzzer, producing a loud, continuous audible warning. The circuit operates on a simple 9V DC supply and is assembled in a water-resistant enclosure. Experimental results demonstrated high accuracy and reliability, with LEDs lighting sequentially as the tank filled and the buzzer triggering instantly upon overflow, remaining active until the water level dropped. Response time remained consistently under 1.4 seconds across all levels and multiple tests. The system offers an affordable, very low-maintenance solution for water conservation. The sensor alarm system transforms a manual, error-prone task into a smart, efficient, and reliable process for managing water storage.
Keywords: Water level indicator, overflow alarm, transistor switching, LED display, buzzer alert.